Generals ten British commanders who shaped the world - Urban, Mark 1961- (Faber and Faber, 2005)
Tells the story of ten exceptional generals who left their mark on Britain, the British Empire, and the world. Some - including the Duke of Wellington, Lord Kitchener and Bernard Montgomery - are names etched in the national mythology